What's new in the pediatric spine? - Ilharreborde, Brice; Helenius, Ilkka; Studer, Daniel; Hasler, Carol; Kruyt, Moyo; Mineiro, Jorge; Ovadia, Dror; Farrington, David; Pesenti, Sebastien; Yazici, Muharrem; EPOS Spine Study Grp (SAGE PUBLICATIONS INC, 2025)
Introduction: The field of pediatric spine surgery has encountered major changes and evolutions lately, with new treatment options available and the development of enabling technologies. This article aims to summarize the most relevant recent literature.
Materials and methods: The five most relevant topics were selected and assigned to one or two authors who performed a comprehensive Pubmed database search for articles published in the last 4 years (2021-2024). Only studies with a high level of evidence or clinical relevance were reported.
Results: Thirty-nine articles were selected and analyzed, covering the following subjects: treatment options in tweeners, the impact of new medical treatments in pediatric spine practice, the emergence of new surgical techniques, the development of enabling technologies in scoliosis surgery, and recent relevant randomized controlled trials.
Discussion: Many new surgical concepts and techniques have been developed lately, but their results need to be further assessed on specific subgroups of patients. Numerous significant medical improvements have been reported in the last 5 years, affecting positively the management of syndromic and neuromuscular patients.